2020
DOI: 10.1111/jocs.15257
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive aortic valve replacement with sutureless bioprosthesis through right minithoracotomy with completely central cannulation—Early results in 203 patients

Abstract: Objectives: Minimally invasive aortic valve replacement (mini-AVR) might improve clinical outcomes, particularly in high-risk and elderly patients. Sutureless/rapid deployment bioprosthesis can offer advantage of decreasing the cross-clamp time (XCT) and easing the procedure. Our aim was to evaluate the safety and perioperative outcomes of mini-AVR using sutureless bioprothesis via the right minithoracotomy approach with our modified technique of central cannulation. Methods: We performed a single-center retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…It is important to highlight the impact of rapid deployment and sutureless valves in facilitating RAMT AVR. Many groups and recent studies have found these valves to be especially useful for the RAMT approach, where they have resulted in comparable durability, shorter intraoperative times and better hemodynamics, while PPM insertion rate has varied based on the center 47–49 . As seen in our cohort, although conventional bioprosthetic and mechanical valves can be implanted via a RAMT incision, 95% of cases were performed by using a rapid deployment of sutureless valve.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It is important to highlight the impact of rapid deployment and sutureless valves in facilitating RAMT AVR. Many groups and recent studies have found these valves to be especially useful for the RAMT approach, where they have resulted in comparable durability, shorter intraoperative times and better hemodynamics, while PPM insertion rate has varied based on the center 47–49 . As seen in our cohort, although conventional bioprosthetic and mechanical valves can be implanted via a RAMT incision, 95% of cases were performed by using a rapid deployment of sutureless valve.…”
Section: Discussionmentioning
confidence: 80%
“…Many groups and recent studies have found these valves to be especially useful for the RAMT approach, where they have resulted in comparable durability, shorter intraoperative times and better hemodynamics, while PPM insertion rate has varied based on the center. [47][48][49] As seen in our cohort, although conventional bioprosthetic and mechanical valves can be implanted via a RAMT incision, 95% of cases were performed by using a rapid deployment of sutureless valve. Finally, there were no conversions to sternotomy, no cases of limb ischemia or vascular complications, and no incidence of infective endocarditis or valve thrombosis.…”
Section: Postoperative Outcomesmentioning
confidence: 76%
“…When the topic is minimally invasive, sutureless aortic valve replacement, we are highly interested, as all cardiovascular surgeons would. We have read with interest the article entitled: "Minimally invasive aortic valve replacement with sutureless bioprosthesis through right minithoracotomy with completely central cannulation-Early results in 203 patients" by Sef et al 1 For sutureless aortic valve implantation; the higher transverse aortotomy is required to be located approximately 0.5 cm above sinotubular junction or 3.5 cm above the aortic annulus. 2,3 The level of transverse aortotomy to be at least 2.5 cm above the sinotubular junction is quite high.…”
Section: Dear Editormentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Since the first report of minimally invasive aortic valve replacement (AVR) in 1993, minimally invasive access has been associated with comparable operative mortality, less bleeding and reduced intensive care and hospital stay when compared to the conventional sternotomy. 11,12,[17][18][19][20] Furthermore, faster recovery, less pain and better cosmesis have been reported in several clinical studies. [21][22][23] In this article, we have reviewed all the available literature on the topic of valve-sparing aortic root replacement (David procedure) via minimally invasive approach through upper hemisternotomy in an attempt to assess current trends and to recognize potential advantages of this technique.…”
Section: Introductionmentioning
confidence: 99%